Patrilineal and Matrilineal Organization in Sumatera: the Batak and the Minangkabau - Khairina, Jikti (Linguistik, Terjemahan, Sastra (LINGTERSA), 2022)
This study is about Matrilineal and Patrilineal descent between the Batak and the Minangkabau culture. Thus, this paper analyzes the view of adults (educated) about the phenomenon in Indonesia, whether the children of those organization confused of the clans of himself/herself. And then this paper aims to elaborate the reasons why adults (educated) people in North Sumatera choose Patrilineal rather than Matrilineal. The research was conducted by using qualitative research. To answer the problems of the study, the data were collected by giving questionnaire. The result of this study were the following; 1) Patrilineal and Matrilineal are supported by the adults (educated) people who participated in filling out questionnaires for this study 2) The reasons why educated people in North Sumatera prefer to choose Patrilineal rather than Matrilineal.